2016
DOI: 10.1124/dmd.116.072140
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolation of Elementary Rate Constants of P-glycoprotein–Mediated Transport from MDCKII-hMDR1-NKI to Caco-2 Cells

Abstract: The best parameters for incorporation into mechanistic physiologically based pharmacokinetic models for transporters are system-independent kinetic parameters and active (not total) transporter levels. Previously, we determined the elementary rate constants for P-glycoprotein (P-gp)-mediated transport (on- and off-rate constants from membrane to P-gp binding pocket and efflux rate constant into the apical chamber) using the structural mass action kinetic model in confluent MDCKII-hMDR1-NKI cell monolayers. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The k 1 for association of substrates to P-gp is essentially the same for all compounds used for model validation (Lumen et al, 2013;Meng et al, 2017a), consistent with a large open binding site on P-gp (Li et al, 2014). The inhibitor dissociation constant K i = k rQ /k 1 , with respect to the inhibitor concentration in the membrane, so the system independence of k 1 allows K i to be calculated for each inhibitor from k rQ alone.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…The k 1 for association of substrates to P-gp is essentially the same for all compounds used for model validation (Lumen et al, 2013;Meng et al, 2017a), consistent with a large open binding site on P-gp (Li et al, 2014). The inhibitor dissociation constant K i = k rQ /k 1 , with respect to the inhibitor concentration in the membrane, so the system independence of k 1 allows K i to be calculated for each inhibitor from k rQ alone.…”
Section: Introductionmentioning
confidence: 60%
“…We can calculate the inhibitor dissociation constant, K i , from P-gp into the membrane from the inhibitor k rQ and k 1 (see Materials and Methods). We have found previously that k 1 is essentially the same for all of the drugs we have studied in both MDCKII-hMDR1-NKI and Caco-2 cells (Agnani et al, 2011;Lumen et al, 2013;Meng et al, 2017a). %CV is the coefficient of variation as a percentage between the data and the fitted data points.…”
Section: Acharyamentioning
confidence: 71%
See 1 more Smart Citation
“…Therefore, a rhodamine molecule needs to be within ∼2.8 nm of a P-gp to allow direct entry into the central binding cavity prior to jumping out of the second energy minimum. Assuming a P-gp density on the cell surface of 100 μm −2 , 30 the average protein− protein distance is 100 nm, and hence the maximum solute− protein distance of 50 nm. Therefore, the probability of a rhodamine diffusing directly from the energy minimum in the bilayer into the central binding cavity is about 5.6%.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In their study, Shirasaka et al found that estimated K m and V max values for quinidine, verapamil, and vinblastine increased with increasing P-gp expression levels. If other transport systems, such as a basolateral uptake transporter 62 or another efflux transporter, is involved in the observed transport of a substrate, then the calculated values for K m and V max becomes convolutions of all transport processes involved, considering the dependency on P-gp expression levels and the potential contribution from other transport systems coexpressed in the cell model. Estimations of K m and V max values will, therefore, be dependent on the used model system.…”
Section: Michaelisementen Analysis and P-gpmentioning
confidence: 99%